PERAN PENGABDIAN MASYARAKAT DALAM UPAYA OPTIMALISASI PEMAHAMAN TRANSLITERASI MAHASISWA UNTUK MENINGKATKAN KUALITAS MAHASISWA PENDIDIKAN BAHASA ARAB - Rustiman, Uus (Yayasan Education and Social Center, 2024)
This activity explores the role of community service in efforts to increase students' understanding of transliteration, especially in Arabic language education. Arabic-Indonesian transliteration is important for students studying Islam and Arabic, involving the process of copying Arabic letters (hijaiyah) into Latin letters and their symbols. The aim of this service is to improve students' skills in using Arabic-Latin transliteration in writing scientific papers. Implementation methods include lectures, discussions, Participatory Rural Approach (PRA), as well as monitoring and evaluation, carried out online. The target of this activity is students of the Arabic Language Education Study Program, Department of Foreign Language Education. The results show high student motivation, easy-to-understand material, and a good level of mastery of Arabic and Indonesian in writing scientific papers using Arabic-Indonesian transliteration rules. It is hoped that this activity can make a significant contribution in optimizing students' understanding of transliteration, supporting improving the quality of Arabic language education